AGE AND BODY MASS INDEX IN TYPE I ENDOMETRIAL CANCER GRADE - Gilang Adi Firmansyah; Dyah Fauziah; Brahmana Askandar Tjokroprawiro (Universitas Airlangga, Surabaya, Indonesia, 2022)
Highlights: 1. The major risk factors for type I endometrial cancer, namely age and obesity, play a major role in the increase in this case and are thought to be related to the grade in these cancer patients.2. Type I endometrial cancer patients at Dr. Soetomo General Academic Hospital 2019-2020 are dominated by patients diagnosed at the age of 56-65 years, having an overweight body mass index (23-24.9 kg/m2).3. The patient's age and body mass index did not correlate with endometrial cancer type I grade. Abstract Background: The increase in obesity and life expectancy has contributed to type I endometrial cancer cases worldwide. Increased risk factors play a role in the increase of these cases. Objectives: To determine the relationship between age and BMI with the cancer grade. Material and Method: This research was a cross-sectional study. The data were obtained from the patient’s medical records. The sampling technique was total sampling. The analysis used was Spearman Rho correlation test for the relationship between age and BMI with cancer grade. Results: This study recorded 54 patients with type I endometrial cancer in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from 2019 to 2020. The patients were from the age group 56-65 years 25 patients (46.30%), 46-55 years 17 patients (31.48%), 36-45 years 8 patients (14.81%), 26-35 years 2 patients (3.7%), and >65 years 2 patients (3.7%). For BMI, the patients were overweight (23-24.9 kg/m2) 21 patients (38.89%), normal (18.5-22.9 kg/m2) 14 patients (25.93%), obesity (25-29.9 kg/m2) 12 patients (22.22%), and obesity II (≥30 kg/m2) 7 patients (12.96%). For grade, grade III were 22 patients (40.75%), grade II 20 patients (37.04%), and grade I 12 patients (22.22%). There was a weak, insignificant positive correlation between age with grade (ρ=0.116, 0.405>α=0.05) and a weak, insignificant negative correlation between BMI with grade (ρ=-0.206, 0.135>α=0.05). Conclusion: A total of 54 patients with type I endometrial cancer at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from 2019-2020 aged 56-65 years and overweight (23-24.9 kg/m2) with grade III cancer. The patient's age and BMI did not correlate with the patient's grade.